Cortesía lingüística: un estudio en el ámbito educativo - Alduntzin García, Iñigo (Huarte de San Juan. Filología y Didáctica de la Lengua, 2014)
Although linguistic courtesy has been extensively investigated among adults, there is no research analysing it in education contexts. This study sets out to highlight the need of having to train secondary school learners in linguistic courtesy. Due to the lack of previous research, some role play activities were done in order to comprehend the situation of linguistic courtesy in the classroom. Students from compulsory and optional secondary education have carried out spontaneous conversations about four different situations. The study analysed the strategies they chose and the structures constructed. The findings revealed that girls and boys tend to choose different strategies and structures in order to face those situations. Furthermore, among teenagers differences are notable depending on their age. That is, it was found that both the sex and age of teenagers (evolutionary stage) are variables of linguistic courtesy.